Repères et filiations : A propos de Nina Bouraoui - Belgacem BELARBI (My University, 2013)
In this thesis, we tried to identify a state of being of a novelist who, unlike other writers, only perpetuates the attempt to go towards the self without getting lost in it. Algeria will represent that home base which, throughout the whole production, seems to function as an obsession. From this forced exile, this cut, Nina Bouraoui will live the uprooting of a being marked by a sense of loss and homelessness. More than a new literary genre, the auto-fiction would refuse the idea of a univocal truth where the subject will put himself in question, being able to achieve himself only through literature, he becomes a subjectin the process of becoming. This work will show how Nina Bouraoui will invent another self, combining fiction and biography, to escape for a moment from her inner labyrinth. Writing oneself would annihilate the border to become someone else. Her words will try to find a focal point, serene and soothing. Transforming and reorganizing the world to the extent of her aspirations, this is the Bouraouian dream.
Keywords: Filiations / auto-fiction/ gender / Algeria / labyrinth / woman / becoming.